Development of Education Gymnastics Video to Stimulate Children’s Motor Skills - Shofiyanti Nur Zuama; Ririn Safitra; Sri Nurhayati; Didik Purwanto; Stevani (CV. Creative Tugu Pena, 2026)
This study is motivated by the low motor physical abilities of children due to a lack of engaging and structured learning stimulation. The study aims to develop an educational exercise video media to stimulate children's motor physical abilities in Group B1 at Samporoa Pembina State Kindergarden. The method used is Research and Development (R&D) with the ADDIE model, including the stages analysis, design, development, implementation, and evaluation. The subjects consisted of 15 children. Data collection techniques used were observation, interviews, documentation, and questionnaires. Validation results showed that the media was highly feasible to use with a percentage of 98.75% from media experts and 98.6% from material experts. Implementation results showed an increase in children's motor abilities in the aspects of coordination, balance, and agility. Thus, educational exercise videos are effectively used to stimulate the development of children's early motor physical skills.